Active oxygen control by a PbO mass exchanger in the liquid lead–bismuth eutectic loop: MEXICO. Issue 1 (2nd January 2017) - Lim, Jun; Marino, Alessandro; Aerts, Alexander
ABSTRACT: Accurate control of dissolved oxygen concentration is crucial in order to use liquid lead alloys as a coolant of advanced nuclear systems. An oxygen control system based on PbO mass exchanger (PbO MX) technology was implemented in order to control the dissolved oxygen concentration in the liquid lead–bismuth eutectic (LBE) loop MEXICO. The oxygen control system consisted of a packed bed of PbO spheres, an oxygen sensor and a pneumatic control valve. The concentration of dissolved oxygen in the loop was controlled by regulating the LBE flow through the PbO MX using a proportional–integral–derivative (PID) controller with feedback from the oxygen sensor. Highly accurate control of the dissolved oxygen concentration in the loop was achieved by this system.